Ekspedisi Senyum Desa Indonesia (ESI) Gerak Sehat Bersama Masyarakat Dusun Merak Situbondo - Umar Faruk; Jatim Desiyanto (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Merak Hamlet is a hamlet located on the north coast in the forest area of Baluran National Park. The distance from the city center takes ± 2 hours. Facilities that are less suitable for use such as health facilities. With this community service, the government can see the back of the peacock hamlet which only controls sunlight for electricity, and can feel routine health checks. With the results of the service uploud in the mass media, the government sees the condition and situation of the peacock hamlet during the day and night. With the motivation of the class all children will not be broken and adults feel free health checks. Polindes became the main target to create a health post with the help of the health center medical team in the city. After the service activity, thank God there was a continuation for Electricity from the government and the merak hamlet is now bright like the city. The return of enthusiasm for learning and public health is now improving with the health check.